Guidance for studies evaluating the accuracy of sputum-based tests to diagnose tuberculosis - Schumacher, Samuel G.; Denkinger, Claudia M. (The journal of infectious diseases, 2019)
Abstract. Tests that can replace sputum smear microscopy have been identified as a top priority diagnostic need for tuberculosis by the World Health Organizati